Analisis Yuridis Kepatuhan Hukum terhadap Karantina Kesehatan (Studi Penelitian Kantor Kesehatan Pelabuhan Kelas II Tanjung Pinang) - Joni Hardi (Wajah Hukum, 2020)
Indonesia is located in the path of international trade traffic with many entrances to Indonesian territory, this is a risk factor for the spread of diseases and health problems.. The purpose of this study was to find out how the health quarantine legal regulation at the entrance to the port in the Class II Tanjung Pinang Port Health Office. This study uses a descriptive approach to the type of normative research and sociology. implementation of quarantine law in the supervision of ship arrivals in accordance with / not in accordance with standard operating procedures) The results showed that Law Number 6 Year 2018 on Health Quarantine which is the basis of the implementation of health quarantine has governed the criminal application of violations by the Quarantine Civil Servant Investigator, and the number of human resources is still lacking in terms of quality / competence, the number of facilities and equipment is still lacking especially in the work area,   The conclusion of this research is the good regulation of the health quarantine law due to the adoption of the criminal article against violators, but it is needed an inter-sectoral legal regulation in implementing quarantine rules by related agencies as well as the addition of tablespoons that have potential in their fields.